An introduction to dengue-disease diagnostics - Darwish, Nadiya Taha; Alias, Y.; Khor, S.M. (Elsevier, 2015)
In this review, we discuss how dengue disease can be diagnosed accurately at the viremia phase and the fever phase. Diagnostic tools currently used to detect dengue virus (DENV) are virus isolation, capture IgM and IgG ELISA, real-time polymerase chain reaction (RT-PCR), and immunochromatography of the dengue NS1 antigen. First, we explain the advantages, the challenges and the limitations of different diagnostic tests. This account is followed by several examples using biosensors for detection of several important DENV biomarkers. Finally, we discuss our opinions regarding future perspectives in this field.